Career progression of graduates in diploma for professional education - Alda, Rivika C.; Boholano, Helen B.; Leon-Abao, Ethel De (Journal of Education and Learning (EduLearn), 2025)
This research delves into the career progression and perceptions of graduates from the Diploma in Professional Education (DPE) Program at Cebu Normal University, spanning the academic years 2016-2020. This aims to analyze demographic profiles, assess knowledge levels in various domains, and explore graduates' regard for the DPE program in their current work. Employing a mixed-methods design, the research gathers data through surveys and virtual interviews. Participants indicate an overall positive assessment of the DPE program and express strong agreement in content knowledge, pedagogical knowledge, technological competence, and the intersection of technology with pedagogy and content. They exhibit strong alignment with the technological pedagogical and content knowledge (TPACK) framework, proving their proficiency in incorporating technology into instruction with ease. Qualitative insights unveil transformative learning journeys, the nurturing of teaching excellence, overcoming challenges with confidence, and the empowerment of future educators as dominant themes in the experiences of DPE graduates. The combination of data sets highlights how well the program communicates knowledge and fosters a constructive, transformative learning environment. The DPE program's good reputation, strong support of TPACK, and noted career progression demonstrate how well it prepares teachers for the ever-changing demands of the classroom and offers valuable insights to improve teacher education.